Bevacizumab for the treatment of glioblastoma. (August 2013) - Chowdhary, Sajeel; Chamberlain, Marc
Glioblastoma (GB) is the most common adult malignant primary brain tumor that arises from glial precursor cells. Survival in GB is variable ranging from 6 to 20 months notwithstanding current standard of care (SOC) treatment. Therapy has improved, but nonetheless GB is still invariably recurrent and incurable. Treatment options at recurrence include re-operation with or without carmustine (BCNU) wafer implantation (Gliadel), re-irradiation and standard/experimental chemo- or targeted therapy. Recurrent GB radiographic response rates to cytotoxic chemotherapy are less than 10% and median 6-month progression-free survival (PFS6) is 15%. With the recognition of the importance of tumor angiogenesis and the development of targeted therapy based on angiogenic inhibition, two pivotal trials of the VEGF-directed monoclonal antibody, bevacizumab (BEV, Avastin), were conducted in recurrent GB. Based upon the results of these two prospective US trials (median radiographic response rate: 25%; PFS6: 40%), BEV as a single agent was granted accelerated approval in the USA for recurrent GB. This review is a summary of current literature and clinical trials research in the role of BEV for the treatment of newly diagnosed and recurrent GB and potential future use of anti-angiogenic therapies in the management of GB.